Nosiruddin Tusi’s Gnoseological and Logical Views as Well as the Author on these Issues Examples from his Works - Umarov ugli (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
This article analyzes the attitude of the famous representative of Arab-Muslim social thought, Nasiruddin Tusi, to the issue of epistemological and logical science. Abu Ja'far Muhammad Nasiruddin Tusi wrote works of great importance in Islamic philosophy and ethics. Philosophical views of the thinker continued the traditions of the ideas of Mashshoyiuna direction.